The Analysis of Informal Reasoning Fallacy and Critical Thinking Disposition Among Malaysian Undergraduates - Ramasamy, Shamala; Fung, Han Ping (AeU, 2015)
In this information age, the amount of complex information available due to technological advancement would require undergraduates to be extremely competent in processing information systematically. Poor critical thinking ability would hinder undergraduates in coping with everyday life situations that may lead them to become gullible citizens. One of the dimensions of critical thinking is informal fallacy, referred to as erroneous thinking. Critical thinking dispositions (CTD) and informal reasoning fallacy (IRF) are integral essence in facilitating students to have high ability in thinking critically. The objective of this study is to examine the performance of IRF ability and CTD among Malaysian undergraduates and also to determine the influence of undergraduates’ background variables to critical thinking. Relationship between IRF and CTD is determined to add to the deficit literature review. Data collection was gathered from 630 undergraduates. Findings reported that a moderate performance was yielded in IRF and CTD constructs. A significant relationship existed between the above mentioned constructs denoting that fallacy detection and CTD are crucial in order to be a critical thinker. Demographic variables were found not to be significant contributors to critical thinking, hence Malaysian undergraduates are not disadvantaged by their background in order to think critically. This discovery may shed light on educators to embark on critical thinking cultivation without the fear of how students’ background may impact the process of critical thinking in classrooms.